2013
DOI: 10.21273/hortsci.48.5.645
|View full text |Cite
|
Sign up to set email alerts
|

Composted Dairy Manure and Alfalfa Hay Mulch Affect Soil Ecology and Early Production of ‘Braeburn’ Apple on M.9 Rootstock

Abstract: A variety of organic mulches and amendments have been observed to improve soil quality and productivity of apple orchards. Alfalfa hay and composted dairy manure solids (CDS) are readily available in the apple-growing region of the Pacific Northwest and British Columbia and could be used to improve orchard performance. The objective of this research was to determine the influences of CDS amendment and alfalfa hay mulch on populations of soil microfauna, soil chemical properties, and early growth; nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
(47 reference statements)
1
12
0
1
Order By: Relevance
“…Además de proveer nutrientes, el mulch podría ayudar en el control de patógenos tales como nemátodos. Efecto que podría durar varios años luego de la aplicación del mulch (Forge et al, 2013;Gliessman, 2007 Oficial de la Tecnología EM en América Latina). Se obtienen mediante fermentación y constituyen una mezcla de levaduras, bacterias productoras de ácido láctico y bacterias fototróficas.…”
Section: Análisis Y Resultadosunclassified
“…Además de proveer nutrientes, el mulch podría ayudar en el control de patógenos tales como nemátodos. Efecto que podría durar varios años luego de la aplicación del mulch (Forge et al, 2013;Gliessman, 2007 Oficial de la Tecnología EM en América Latina). Se obtienen mediante fermentación y constituyen una mezcla de levaduras, bacterias productoras de ácido láctico y bacterias fototróficas.…”
Section: Análisis Y Resultadosunclassified
“…Water holding capacity was ranked as the lowest primary benefit with a significant difference ( p < 0.001) in the distribution between usage groups and a higher ranking by nonusers. Improved microbial diversity and greater availability of essential nutrients are examples of benefits to soil biology from OMA in orchards (Brown and Tworkoski, 2004; Forge et al, 2013; Mathews et al, 2002; Peck et al, 2011). The lack of differences for soil biology as the primary benefit between usage groups suggests the perception of the benefit by nonusers is supported by the experience of users.…”
Section: Resultsmentioning
confidence: 99%
“…Organic matter amendments offer multiple benefits by providing a source of essential nutrients and a partial substitute for chemical fertilizer (Bittenbender et al, 1998; Mordoğan et al, 2013; Preusch and Tworkoski, 2003; Roosta and Mohammadi, 2013) while maintaining or improving yields (Amiri and Fallahi, 2009; Baldi et al, 2010; Forge et al, 2013; Sanchez et al, 2003) and improving soil health (Briones et al, 2011; Mathews et al, 2002; van Overbeek et al, 2010). Soils commonly used for orchard production can be at greater risk for carbon loss (Angers et al, 2011).…”
mentioning
confidence: 99%
“…In addition, compost applications in coarse soil increased apple leaf N by 5%, K by 4%, Mn by 13%, and Zn by 5% compared with an unfertilized control (Sas-Paszt et al, 2014). However, compost applications do not appear to affect the vegetative growth or fruit yield or quality independent of soil texture (Forge et al, 2013;Neilsen et al, 2014;Rumberger et al, 2004;Sas-Paszt et al, 2014;Yao et al, 2006). In contrast to the results observed in apple orchards, Baldi et al (2010) found that when compost was tilled into fine textured soil to a depth of 25 cm in a 7-year-old peach orchard, fruit yield increased by 38% in the first year, as did soil quality measures such as, OM, soil mineral nutrition, and microbial biomass C compared with the unfertilized control.…”
mentioning
confidence: 92%
“…One approach to improving soil fertility and reducing N loss is to use carbon-based amendments, such as composts. In apple orchards, compost applications have been shown to improved edaphic properties, including soil OM, microbial biomass carbon (C), microbial respiration, and soil mineral nutrition in fine-and coarse-textured soils (Forge et al, 2013;Neilsen et al, 2014;Rumberger et al, 2004;Sas-Paszt et al, 2014;Yao et al, 2006). For example, Kramer et al (2006) observed that compost amended soils had 42% greater OM and 35 and 57% greater microbial biomass C and N, respectively, than soil fertilized with mineral N fertilizer.…”
mentioning
confidence: 99%